The Impact of the Awareness of Employees in Public Health Sector in Wadi Addawasir: The Importance of the Application of Total Quality Management )TQM( Principles For Achieving Goals «A Field Study» - Abbas, Anas (The Arab Journal of Administration, 2019)
The aim of the study is to assess the extent to which the employees of the public health sector in Wadi Addawasir understand the importance of implementing the principles of Total Quality Management (TQM) in order to achieve the desired goals. The study also aims to evaluate the changes made by the hospital manage- ment to adopt the TQM approach in its work, and the application of TQM principles. In order to achieve the objectives of the study, a questionnaire was designed to be distributed to a sample that is consistent with the research community and judged by a group of experts in administrative and statis- tical sciences. The researcher used the Statistical Package for Social Sciences (S.P.S.S) to describe and analyze data. The new scientific literature was studied in the field of study through digital and paper libraries, and was made available from the internet sites, as well as the previous studies that were close to the field of study in the subject to benefit from and build on them. The results of the study showed that there is a feeling of workers in the health sector in Wadi Addawasir that there are theoretical and scientific plans to implement the principles of total quality, but lack activation and follow-up by the higher authorities. The weakness of the role of public relations in the field of study has also been reflected in the pressure of work on the part of hospital staff, and often by the beneficiaries of this sec- tor. The results of the study showed that the quality of the training and its effectiveness reflected positively on the quality of medical services provided in the health sector in Wadi Addawasir. The effectiveness of the train- ing leads to improving the quality of services provided by the general hospital and its health centers in general. The study recommended the need to create a general atmosphere supportive of quality by decision mak- ers and service providers in all departments engaged in the provision of health services through the start of the Division of Quality Assurance. And to work on the preparation of training and educational programs that illustrate the concepts of quality, and dissemination of culture among the workers in all sectors of health, and the creation of a department to monitor the quality of training and medical services in each hospital through the criteria and indicators required to implement the entry TQM. The study also recommended working on strengthening the relationship between health sectors and universities as research and academic institutions through benefiting researchers and postgraduate students and hosting experts to hold training courses, semi- nars and conferences in the field of quality of health services.